Strategy Management School Kindergartensanta Lusia Medan Region for Accreditation - Saloma Banjarnahor; Yuniarto Mudjisusatyo; Darwin Darwin; Syawal Gultom (Budapest International Research and Critics University, 2023)
The purpose of this research is to analyze the strategic management plan for the Santa Lucia Kindergarten unit in the Medan area, the implementation of the early childhood education management strategy and the results of the strategic management review of early childhood education. In this study used a qualitative descriptive method carried out by field studies. The research was conducted at Santa Lusia Kindergarten in Medan. Data collection techniques were carried out through interviews, observation and documentation. The results of the study show that the strategic management process begins with strategic planning at Santa Lusia Kindergarten in Medan or Strengths Weaknesses Opportunities Threats analysis. Based on the Accreditation Standards for the Early Years, there are two standards that do not meet the criteria, namely Standard 4, Standards for Educators and Education Personnel. By using a Strengths Weaknesses Opportunities Threats analysis, it is known that the strength of Santa Lusia Kindergarten in the Medan region lies in its dense population, sources of funding, and opportunities to play and learn. The weakness lies in the incomplete teacher qualifications and limited teaching staff. This opportunity lies in the support of parents, central and regional government support, as well as a conducive school environment. Meanwhile, the challenge lies in the number or addition of other educational institutions around schools and the thinking of the community which is still dynamic. Then planning will be carried out by grouping the offerings according to age, involving teachers in seminars and workshops and adding activities for Santa Lusia Kindergarten students in the Medan area. The implementation of the management strategy consists in the fact that trainers participate in seminars and workshops and improve their activities. Evaluation of strategic management results is very important for the recruitment of training personnel.